การแยกสกัดทองแดงจากกากตะกอนชุบโลหะโดยวิธีการสกัดด้วยตัวทำละลาย - ธนภัทร ขวัญพันธ์งาม (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Wastewater from the plating process normally contains various heavy metals. It is usually treated by precipitating into sludge in the forms of metal oxides such as copper (II) oxide, nickel (II) oxide, and chromium trioxide before sending out for disposal. Therefore, works have tried to recover those metals to reduce the use of natural resources and hazardous waste and gain economic benefits. This project aims to recover copper and study the efficiency of copper recovery using solvent extraction method. The experiment was divided into 4 steps: 1) characterize physical and chemical properties of the sludge 2) optimize conditions for copper extraction from plating sludge by the solvent extraction method using LIX 84-IC diluted in hexane at the laboratory scale by following parameters: pH, LIX 84-IC concentration, and the number of extraction cycles. 3) commission the extraction column at pilot scale 4) study the efficiency of copper extraction in the extraction column pilot scale using the results from the laboratory scale. The preliminary study selective extraction of copper was showed the optimal conditions for the initial pH of aqueous phase was 3 with 5% (%v/v LIX 84-IC to hexane) and 4 stages, which gave a copper extraction efficiency of 99.00%. When taking the conditions from the laboratory to evaluate in the extraction column at the pilot scale, it was found that the copper extraction efficiency was 39.73%.